2021
DOI: 10.3390/mi12121530
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Performance of a Passive Micro-Mixer with Mixing Units Stacked in Cross Flow Direction

Abstract: A new passive micro-mixer with mixing units stacked in the cross flow direction was proposed, and its performance was evaluated numerically. The present micro-mixer consisted of eight mixing units. Each mixing unit had four baffles, and they were arranged alternatively in the cross flow and transverse direction. The mixing units were stacked in four different ways: one step, two step, four step, and eight step stacking. A numerical study was carried out for the Reynolds numbers from 0.5 to 50. The correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…The fluid was considered incompressible and Newtonian, with a density of 10 3 kg/m 3 , a dynamic viscosity of 10 –3 Pa·s, and a diffusion coefficient of 10 –9 m 2 /s, as common reference values in micromixer studies. Also, the steady-state condition was selected to evaluate the numerical simulations. Equal uniform velocity was set to both of the inlets, along with applying the molar concentrations (mol/m 3 ) of 0 and 1 to inlet 1 and inlet 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The fluid was considered incompressible and Newtonian, with a density of 10 3 kg/m 3 , a dynamic viscosity of 10 –3 Pa·s, and a diffusion coefficient of 10 –9 m 2 /s, as common reference values in micromixer studies. Also, the steady-state condition was selected to evaluate the numerical simulations. Equal uniform velocity was set to both of the inlets, along with applying the molar concentrations (mol/m 3 ) of 0 and 1 to inlet 1 and inlet 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al [ 30 ] proposed a 3D cross-linked double-helix micromixer, studied the fast mixing process under a low Re number by using a numerical method, and found that mixing units such as split recombination, chaotic advection and flow impact could improve mixing efficiency in the microchannel. Juraeva et al [ 31 ] proposed a passive micromixer stacked with eight mixing cells, in which each mixing cell was provided with a baffle to make the fluid disturbance in the channel stronger and the mixing efficiency higher. Xia et al [ 32 ] proposed a chaotic mixer with a gap and a baffle structure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, passive micromixers use geometric structures to generate chaotic fluid flow without any moving parts, making them simpler, less expensive, and more cost-effective to integrate into various microfluidic systems. Various geometric structures and modifications, such as twisting of the micromixer wall [ 12 ], a staggered herringbone design [ 13 ], blockage in the junction of the fluid stream [ 14 ], surface grooves and baffles [ 15 , 16 ], split-and-recombine (SAR) units [ 17 , 18 ], Tesla structure [ 19 , 20 ], stacking of the mixing units in the cross-flow direction [ 21 ], stacking in the lateral direction [ 22 ] and submergence of the mixing unit [ 23 ], have been studied to generate chaotic flow fields. However, most passive micromixers only show effective mixing in a limited range of Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%